The Construction of Terror Communicating of ISIS News In Social Media - Ellys Lestari Pambayun (UIN Sunan Kalijaga Yogyakarta, 2018)
Global era with its advanced technology has provided small terrorist groups a powerful instrument—social media which is intentionally or unintentionally used to serve their interest. As believed, the terrorist does their action by giving significant impact to publicity. As a terrorist organization, ISIS realized the potentials of social media-oriented terror, in terms of its effectiveness in reaching huge audiences. The spread of the ideology, which is called jihadi virus, is limited in the physical world, however it is possible to spread within social media regardless of time and space. Discursive framework method in constructivism paradigm has led to a conclusion that reality constructed in social media such as twitter, facebook, whatsApp, BBM, path, and other applications are carefully planned in a form of disinformation tactics (propaganda), economic pressure, socio-cultural, and ideology. The impact of social media reveals interesting results that ISIS has formed symbolizations and image changes and raised attention towards the issue. In communication terrorism Joseph Turman’s approach, as one of constructionist approach, it analyzed that ISIS actions are rhetorical actions (such what messages are conveyed, whether it is a persuasive meaning and symbols that appear; acts of terrorism that is produced and delivered to the wider world; elements of rhetoric including labels, definitions, and symbolism in terrorism; public orator about terrorism; and the relationship between terror and the media), in both written and spoken language, there is always possibility for manipulation and receptive communication.[Era global dengan perkembangan teknologinya seakan telah memberi kelompok teroris suatu instrumen yang kuat- media sosial secara sengaja atau pun tidak sengaja untuk melayani hasrat mereka. Bahkan diyakini lebih dari itu, tindakan teroris sendiri tidak akan berdampak bila tidak terpublikasi secara luas. Organisasi teroris ISIS sangat menyadari potensi media sosial sebagai sarana yang dapat diorientasikan pada aksi-aksi teror mereka, dengan kata lain secara efektif untuk meraih audiens yang besar. Media sosial seperti tweeter, facebook, whatsapp, BBM, path, ipad, dan aplikasi jaringan lainnya tampaknya memang mampu mempromosikan perbuatan-perbuatan mereka secara efektif. Dampak lintas media sosial mengungkapkan hasilnya bahwa ISIS mampu memainkan simbolisasi dan citra dan meningkatkan tensi kepentingan pada isu-isu seputar mereka. Melalui “teori Communicating Terorrism” yang dilahirkan Joseph Turman (2010) menjelaskan bahwa aksi-aksi ISIS bisa dikatakan lebih dari tindakan retorika (sebagai suatu simbol-simbol dan pesan-pesan), yang mereka tuliskan dan ungkapkan melalui bahasa yang penuh makna, yang berpotensi selalu manipulatif dan komunikasi yang reseptif. Penyebaran ideologi, sebagai apa yang kita sebut sebagai virus jihad, yang terbatas pada dunia nyata, tapi melalui media sosial isa menjadi keluarga dan teman tanpa batas ruang dan waktu, membantu memperluas landasan dan percepatan radikalisasi dan perekrutan angota teroris.]